The Use of a Novel Heart Failure Agent in the Treatment of Pregnancy-Associated Cardiomyopathy - Vamsi C. Gaddipati; Aarti A. Patel; Adam J. Cohen (Case Reports in Cardiology)
Peripartum cardiomyopathy is an uncommon, pregnancy-related form of dilated cardiomyopathy that is associated with development of new-onset left ventricular dysfunction. Its etiology is presently unknown, but current standard of care involves the use of typical drug therapy for the treatment of heart failure. Pregnancy-associated cardiomyopathy (PACM) is a similar condition that refers to patients who develop such symptoms prior to the last month of pregnancy. We report the case of a nulliparous Caucasian female who develops early, severe PACM during her first pregnancy with postpartum persistence of New York Heart Association class II-III symptoms despite medical therapy. The use of the novel heart failure agent, sacubitril/valsartan (Entresto), is initiated with near-complete resolution of her symptoms.